1993
DOI: 10.1210/endo.133.1.8391426
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment of rats with the antidepressant amitriptyline attenuates the activity of the hypothalamic-pituitary-adrenocortical system.

Abstract: The effects of the tricyclic antidepressant amitriptyline on the rat hypothalamic-pituitary-adrenocortical (HPA) system were studied. The time-course experiments showed that amitriptyline, given via the drinking water (4.5 mg/kg.day), produces significant decreases (P < 0.05) in adrenal weight after 5 (-20%) and 7 weeks (-21%) of treatment. Hippocampal mineralocorticoid receptor (MR) levels were down-regulated at days 3 (-27%) and 7 (-20%), and transiently up-regulated at 2 (+40%), 5 (+74%), and 7 (+18%) weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
87
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(103 citation statements)
references
References 38 publications
14
87
2
Order By: Relevance
“…Moreover, chronic treatment with fluoxetine, as well as other antidepressants, significantly elevated the levels of glucocorticoid receptors in the hippocampus (Brady et al 1991(Brady et al , 1992, which normally mediate the negative feedback response to stress-induced activation of the HPA axis (Sapolsky et al 1984). Finally, our results are in agreement with previous studies in experimental animals (Reul et al 1993) and in healthy humans (Michelson et al 1997), which reported that chronic treatment with antidepressants markedly attenuated the pituitary-adrenal response to stressful or pharmacological challenges. Although the role of CRH in mediating the anorexic effects of LPS has not been studied directly, there are indications that CRH mediates the anorexic effects of IL-1 (Bluthe et al 1992;Uehara et al 1989).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, chronic treatment with fluoxetine, as well as other antidepressants, significantly elevated the levels of glucocorticoid receptors in the hippocampus (Brady et al 1991(Brady et al , 1992, which normally mediate the negative feedback response to stress-induced activation of the HPA axis (Sapolsky et al 1984). Finally, our results are in agreement with previous studies in experimental animals (Reul et al 1993) and in healthy humans (Michelson et al 1997), which reported that chronic treatment with antidepressants markedly attenuated the pituitary-adrenal response to stressful or pharmacological challenges. Although the role of CRH in mediating the anorexic effects of LPS has not been studied directly, there are indications that CRH mediates the anorexic effects of IL-1 (Bluthe et al 1992;Uehara et al 1989).…”
Section: Discussionsupporting
confidence: 92%
“…Our preferred model is that desipramine initially increases hippocampal GR translocation and function in both mice groups; the increased GR translocation and function lead to both the reduced corticosterone levels (following enhanced negative feedback) and the GR downregulation (following GR internalization into cellular nuclei). This model is supported by studies in rats, where antidepressants decrease HPA axis activity and induce GR downregulation within the first few days of treatment (Reul et al, 1993;Yau et al, 2001), and by studies in vitro, where antidepressants induce GR translocation and GR downregulation within one or 2 days of treatment (Pariante et al, 1997(Pariante et al, , 2003aOkugawa et al, 1999;Yau et al, 2001;Heiske et al, 2003). Indeed, Mukherjee et al (2004) found that one single dose of imipramine in mice induces GR translocation in the CA1 subregion, the same area where we find the GR downregulation.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, even if brain levels of desipramine were increased in abcb1ab (À/À) mice, there is no evidence that higher doses of tricyclic could lead to hippocampal GR downregulation rather than upregulation. In fact, one study in rats treated with amitriptyline (for 5 weeks) have found no evidence of hippocampal GR downregulation even using a dose that was 15-fold larger than the minimal dose able to induce GR upregulation (Reul et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Brains were rapidly removed from the skull, the hippocampus and hypothalamus were dissected and the anterior pituitary was collected. Dissected tissues were instantaneously frozen in liquid N 2 and stored at Ϫ80ЊC until corticosteroid receptor assay as described elsewhere (Reul et al 1993 …”
Section: Adrenalectomy Tissue Collection and [ 3 H]-steroid Binding mentioning
confidence: 99%
“…In a separate set of experiments, the MR and GR concentrations were assessed by a soluble corticosteroid binding assay (Reul and de Kloet 1985;Reul et al 1993). For the corticosteroid binding experiments, male HAB (n ϭ 11) and LAB (n ϭ 10) rats were bilaterally adrenalectomized (ADX; via the dorsal approach under halothane anesthesia) between 7 A.M. and noon, i.e.…”
Section: Adrenalectomy Tissue Collection and [ 3 H]-steroid Binding mentioning
confidence: 99%